Postulato di conoscenza di Dio per esperienza secondo George Tyrrell e la sua valutazione teologica - Borto, Paweł (Bogoslovni vestnik, 2024)
The purpose of this article is to present the critical evaluation of George Tyrrell’s postulate concerning the knowledge of God by experience. The postulate was born from the criticism directed towards the way of conceiving the knowledge of God in Neo-Scholasticism – the way that only took into consideration the intellectual dimension. To achieve this goal, the first step was to in-dicate when and why the Irish theologian passed from one who followed neo- -scholastic positions to one who severely criticized “scholasticism”. In the second part of the article, Tyrrell’s way of understanding the notion of religious experience is specified, that is, of understanding it as a revelation of God in its primordial aspect. As a third point, it is presented how Tyrrell himself tried to respond to the greatest problem of his conception of religious experience, namely that of the relationship between the objective and subjective dimensions of truth in religious experience. The last part of the article presents both the negative evaluation by the Magisterium during the modernist controversy of Tyrrell’s postulate, and the perspective opened up by the Second Vatican Council which allowsfor a positive evaluation of the postulate itself, without giving in to errors present in Tyrrell’s conception
Keywords: cerkveno učiteljstvo; conoscenza di Dio; esperienza religiosa; knowledge of God; Magistero della Chiesa; modernism; modernismo; modernizem; razodetje; religious experience; revelation; rivelazione; spoznanje Boga; the Church’s Magisterium; Tyrrell, George; verska izkušnja